The role of training programs in improving the performance of executive management personnel – A Field study for employees Al Baha Province Emirate – - Albarakati, Mohammed Saeed; Felemban, Kamal Nawawy (Journal of Economic, Administrative and Legal Sciences, 2021)
The main objective of this study was to clarify the role of training programs on the performance of executive management employees in Al Baha Province Emirate. In order to achieve the objectives of the study, the researcher relied in preparing his study on the descriptive-analytical approach, in addition to using the questionnaire as a main tool and method for data collection. With the use of SPSS V23 statistical software for data analysis. The study population consisted of all the employees of the executive administration in Al Baha Province Emirate, whose number is 137 employees, and the researcher chose a simple random sample of 101 employees. Through analyzing the data, the researcher reached several important results, the most prominent of which are: There is a direct positive relationship between the role of training programs and the level of improvement of performance of employees in all its dimensions (Improving career decision-making, Improving the process of dealing with the beneficiary, Improving the process of cognitive self-development, Improve production process and capacity, Improve the problem-solving process) In Al Baha Province Emirate Diwan. There are no statistically significant differences at the significance level (α ≤ 0.05) between the averages of the responses of the study sample about the role of training programs in improving the performance of the executive management employees in the Diwan of Al Baha Province Emirate due to the personal characteristics of the individuals of the study sample. Based on the findings of the study, the Study recommends several recommendations, the most important of which are: Work to increase the number of training programs related to developing the employees cognitive capabilities that contribute to developing their level of performance within Al Baha Province Emirate Diwan. Training the employees of Al Baha Province Emirate Diwan on how to work in teamwork and accomplish various job tasks.